2024
DOI: 10.1021/jacs.3c06030
|View full text |Cite
|
Sign up to set email alerts
|

Iron Heme Enzyme-Catalyzed Cyclopropanations with Diazirines as Carbene Precursors: Computational Explorations of Diazirine Activation and Cyclopropanation Mechanism

Torben Rogge,
Qingyang Zhou,
Nicholas J. Porter
et al.

Abstract: The mechanism of cyclopropanations with diazirines as air-stable and user-friendly alternatives to commonly employed diazo compounds within iron heme enzyme-catalyzed carbene transfer reactions has been studied by means of density functional theory (DFT) calculations of model systems, quantum mechanics/molecular mechanics (QM/MM) calculations, and molecular dynamics (MD) simulations of the iron carbene and the cyclopropanation transition state in the enzyme active site. The reaction is initiated by a direct di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…The results showed that for the WT-RCs and EF1, EF2, and EF4 clusters for the LVRQ variant, the substrate was positioned at distances greater than the reactive range from the CC atom, classifying these states as unreactive (see Table S2). Consistent with other carbene transfer studies, all reactive clusters for the LVRQ, LVRQL, GLVRSQL, and GLAVRSQLL variants, with closed shell singlet spin state, demonstrated a concerted reaction mechanism, lacking stable intermediates and characterized by the asynchronous formation and breaking of bonds. Initially, the CC and substrate C1 atom bond formation and elongation of the Fe–CC bond is favored, followed by complete breaking of the Fe–CC bond, culminating in the bond formation between CC and C2. For the LVRQ variant with EF3, the Gibbs free energy barrier was identified as 28.8 kcal/mol, coupled with a product stabilization energy of −36.2 kcal/mol.…”
Section: Resultssupporting
confidence: 75%
“…The results showed that for the WT-RCs and EF1, EF2, and EF4 clusters for the LVRQ variant, the substrate was positioned at distances greater than the reactive range from the CC atom, classifying these states as unreactive (see Table S2). Consistent with other carbene transfer studies, all reactive clusters for the LVRQ, LVRQL, GLVRSQL, and GLAVRSQLL variants, with closed shell singlet spin state, demonstrated a concerted reaction mechanism, lacking stable intermediates and characterized by the asynchronous formation and breaking of bonds. Initially, the CC and substrate C1 atom bond formation and elongation of the Fe–CC bond is favored, followed by complete breaking of the Fe–CC bond, culminating in the bond formation between CC and C2. For the LVRQ variant with EF3, the Gibbs free energy barrier was identified as 28.8 kcal/mol, coupled with a product stabilization energy of −36.2 kcal/mol.…”
Section: Resultssupporting
confidence: 75%